Removal of organic dyes from aqueous solutions by powdered activated carbon adsorption combined with membrane microfiltration - Jiránková, Hana; Doleček, Petr; Šiška, Bedřich; Cakl, Jiří (Univerzita Pardubice, 2008)
This contribution deals with study of the combined adsorption-membrane process for organic dye removal. Adsorption equilibrium and kinetics of Egacid Red sorption on powdered activated carbon (PAC) were studied in batch experiments. From the experimental data the parameters of Langmuir adsorption isotherm and rate constants were determined. During the combined hollow fibre membrane microfiltration operated in dead-end mode it was found that membrane was effective for removal of PAC particles from water suspensions, and PAC tendency for irreversible membrane fouling was extremely low. The presented combined adsorption-membrane process has a potential application for organic dye removal.